TOWARDS THE ANALYSIS OF VERBAL TEXT INTELLIGIBILITY IN CONTEMPORARY VOCAL MUSIC (Mūzikas akadēmijas raksti, 2024)
The inquiry in the problem of the verbal text intelligibility is in the focus of the article. The verbal text in the musical work can preserve or, on the contrary, lose its communicative potential. The research on verbal text intelligibility is a complex and multidimensional issue, which requires an interdisciplinary approach. Four main factors that influence the verbal text intelligibility, are related to the performer, listener, environment and composer’s approach. The inquiry in all four factors is essential, though each of them can be discussed also separately. This article relates to the inquiry of the fourth factor – the music and text conjunction (composer’s approach). The purpose of many contemporary composers is not to reflect the meaning of text in a comprehensive level. The priority often becomes a musical text itself, where the verbal text functions as one of the musical elements. The communication of verbal text is influenced by many factors of music and word relationships – vocal style, reflection of prosody, tessitura, the text condition, texture and one special factor – the realisation of verbal text. The analysis, which is focused on the intelligibility level of the verbal text within the score, will be presented with short excerpts from the choral composition Le Temps scintille... (2003) by Latvian composer Mārtiņš Viļums.